Hydrogen production from excess power in small hydroelectric installations - Yumurtaci, Z; Bilgen, E (PERGAMON-ELSEVIER SCIENCE LTD, 2004)
A brief review shows that hydrogen production from small hydraulic power systems is thermodynamically and technically feasible. Particularly, excess power in existing installations may be used to make the hydrogen production economically feasible. In this study, a simulation model has been developed regarding hydraulic power and hydrogen production systems, and a cost and economics to find out the economical feasibility of hydrogen production. The simulation code is used to carry out a parametric study of small hydraulic power-hydrogen production systems, and also feasibility of existing hydraulic power stations in a case study. In the latter case, the data from 13 installations in Turkey have been used. It has been found that the hydrogen production rate is about 100 ton/year/MW installed power of electrolytic process plant and the cost varies from 3.9 to 8.6 $/GJ (0.55 to 1.21 $/kg) when the hydrogen production plant capacity factor is above 50%. (C) 2003 International Association for Hydrogen Energy. Published by Elsevier Ltd. All rights reserved.
Keywords: hydrogen; electrolytic; hydropower; excess power; PILOT PROJECT; ENERGY; Chemistry; Electrochemistry; Energy & Fuels